Occupational hazards and bladder cancer—An umbrella review of the risk in workers exposed over the past 30 years - Mandanach, Cristina; Handra, Claudia Mariana; Rascu, Agripina; Hohor, Sorina; Gurzu, Irina Luciana; Otelea, Marina Ruxandra; Rascu, Alexandru Stefan Catalin (Frontiers in Public Health, 2025)
BackgroundOccupational exposure accounts for the second preventable risk factor for bladder cancer (BC), after smoking.ObjectiveThis study aimed to extract evidence-based data from the systematic reviews that included studies primarily from the past 30 years, based on a clearly defined method of exposure assessment.MethodsA literature search in PubMed, Web of Science, ScienceDirect, and Embase was conducted using variations of the keywords “BC,” “occupational exposure,” and/or “occupation.” The inclusion criteria for the umbrella review were the following: systematic reviews and meta-analyses focused on occupational exposure, with a clear definition of the exposure assessment, a risk estimate for BC, and a majority of data from 1993 to 2023. We did not include other forms of reviews or systematic reviews focused on the general population and environmental exposure. Data were synthesized based either on occupations or on occupational hazards. After the overlap checking, the remaining reviews were assessed for quality using AMSTAR 2 criteria and afterwards classified for high, moderate, or low evidence using the GRADE scale.ResultsWe found relevant associations with a high level of evidence for firefighters, hairdressers, painters, workers in the petroleum industry, and dry cleaners exposed to tetrachloroethylene. Concerning hazards, exposure to ortho-toluidine was also confirmed to be a risk by recent studies. Welders, veterans, and those exposed to hexavalent chromium at higher risk need more well-designed studies to be confirmed.ConclusionDespite longstanding recognition of certain risks, occupational exposure remains insufficiently investigated. Recent data support the inclusion of occupations and hazards in the individual risk assessment for BC.